Knowledge about the safe use of pesticides by farmers from Central Northern Paraná State - Janaína Zorzetti; Pedro Manuel Oliveira Janeiro Neves; Patricia Helena Santoro; Kelly Christiane Constanski (Semina: Ciências Agrárias, 2014)
Pesticides are considered an important risk factor for human health and have been the subject of several studies, both for its toxicity and environmental degradation. This study aimed to diagnose the knowledge level of farmers from the Central Northern Paraná State on the safe pesticides use. For this we used a questionnaire that addressed issues related to intoxication, use of personal protective equipment (PPE) and knowledge about inserts and labels. We interviewed 100 farmers affiliated to cooperatives in the region. After analyzing the responses, we observed that most farmers did an incomplete use of PPE in their daily activities, or did not use it, as it was found in all cases of poisoning. The terms used in the pesticides inserts and labels are not properly understood by farmers, contributing to increased problems in the safe handling of these products. The study concludes that it is necessary to have a process of training and guidance from regulators and the companies involved, as inputs companies, cooperatives and technical assistance agencies aiming more judicious use of the products and decreasing the risks to health of rural populations and environment.